ANALISIS ASUHAN KEPERAWATAN LATIHAN FISIK INTRADIALISIS DENGAN TERAPI RANGE OF MOTION (ROM) TERHADAP ACTIVITY DAILY LIVING PADA PASIEN HEMODIALISA - Regita Siti Nurjanah (2023)
Hemodialysis is a kidney replacement therapy performed by patients with chronic kidney disease. Hemodialysis therapy has side effects such as cramps, stiffness in the muscles, weakness, dizziness, joint stiffness, and numbness. This effect often occurs when patients undergo hemodialysis, but sufferers have difficulty dealing with these complaints for a long time, causing a decrease in Activity Daily Living. The purpose of this study was to assist patients in increasing their Daily Living Activity by performing Intradialysis Range of Motion (ROM). The administration of this therapy was carried out at the Gatot Soebroto Army Hospital with a total of two patients. Intradialysis Range of Motion (ROM) therapy was carried out five times for three weeks. The effectiveness of therapy was measured using the Barthel Index questionnaire. Where the results of giving Range of Motion Intradialysis therapy were effective in increasing Activity Daily Living as evidenced by the results of the Barthel Index score for both patients which increased after being given this therapy for three weeks.